Multi-autosomal chromosome aberrationsrole in primary amenorrhea - Almukhtar, Asma A. (Iraqi Journal of Cancer and Medical Genetics, 2014)
Primary amenorrhea which result commonly from sex chromosome aberration as geneticabnormalities, may result from oneaberration in autosomal chromosomes or in association with sex chromosomal aberrations. Chromosomal analysis was performed for the 26 years old lady (married and infertile) with primary amenorrhea by using G-band technique. Four autosomal chromosomes are involved in producing primary amenorrhea with normal phenotype, secondary characteristics were associated with mosaic karyotypes the 1st: 46,XX,(3;5;10)(q13-23;q23-35;22-25),(5;19)(qter;p13.2),del(19p13.2). 2nd: 45,XX, ,(3;5;10)(q13-23;q23-35;22-25),del(12),del(12),del(19p13.2),(M). The sex chromosomes look normal.The conclusion was that may be some autosomal chromosomes regulate reproductive development and may the alerted regions on chromosomes in recent study have effect somehow on regulation of reproductive development.